The Efficacy of Putrimalu Root Extract (Mimosa pudica) Against Mortality and Histopathological of Rat Muscles Injected Naja sputatrix Venom - Rendragraha, Briantono Willy; Legowo, Djoko; Kuncorojakti, Suryo; Chusniati, Sri; Arimbi, Arimbi (Universitas Airlangga, 2022)
The purpose of this experiment was to know the effect of Mimosa pudica root extract (normal water extraction) on mortality and muscle histopatological in experimental animal (Rattus norvegicus) which injected with LD50 of Naja sputatrix venom. Fresh Mimosa pudica root dried without sunshine and ground into coarse powder with steamroller (mash 3mm). Plant extract were prepared by stirring 4 g of the powder into 200 ml of water for 3 hours at room temperature and filtered with muslin cloth before freezdried. 30 rat divided into five groups, P0(C+), P1(C-) P2, P3, and P4. P0 (positive control group) injected by saline intra muscular and given aquadest peroral after five minutes, P1 (negative control) injected with Naja sputatrix venom and given aquadest peroral after five minutes. P2, P3, and P4 injected by Naja sputatrix venom and given Mimosa pudica extract with 250mg/KgBW, 500mg/KgBW, and 1000mg/KgBW doses. All of the experimental animal observed about six hours and than euthanized, musculus gluteus maximus (location of injection) was taken for histopatological examination. In this experiment observed that the normal water extraction of mimosa pudica can't reduce mortality of experimental animals but it can decrease muscle damage in 1000mg/KgBW dose.